A new species of Dahlia (Asteraceae, Coreopsideae) from the state of Oaxaca, Mexico - Villaseñor, José Luis; Redonda-Martínez, Rosario (Phytotaxa, 2018)
Dahlia calzadana Villaseñor & Redonda-Mart. (Asteraceae, Coreopsideae), a new species from the district of Cuicatlan, state of Oaxaca is described and illustrated. It grows in the ecotone between the seasonal dry tropical forest and the Quercus forest. This new taxon differs from all other known species of Dahlia by its simple, conspicuously petiolate leaves and its white with pink tones ray florets.